(untitled) (International Journal of Engineering and Computer Science, 2013)
Personal Health Records (PHRs) has emerged as a patient centric model of health information management and exchange. It stores the PHRs electronically in one centralized place in Third Party Cloud Server. It greatly facilitates the management and sharing of patient’s health information and also has serious privacy concerns about whether these service providers can be fully trusted. To facilitate quick development of cloud data storage and preserve the security assurances with outsourced PHRs, the efficient method have been planned. To ensure the patients control over their own privacy homomorphic encryption has been proposed with data auditing to authenticate the accuracy of PHRs stored in cloud server